2019
DOI: 10.21273/horttech04437-19
|View full text |Cite
|
Sign up to set email alerts
|

On-farm Evaluations of Wood-derived, Waste Paper, and Plastic Mulch Materials for Weed Control in Florida Container Nurseries

Abstract: Mulches have been evaluated extensively as a weed management tool in container plant production, but most research has focused on loose-fill wood-derived mulch materials, such as pine bark or wood chips. In this experiment, pine (mixed Pinus sp.) bark (PB), shredded hardwood (HW), and pine sawdust were evaluated for weed control and crop response both alone and in combination with a guar gum tackifier alongside a plastic film mulch, a paper slurry mulch, and the paper slurry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
(36 reference statements)
1
15
0
1
Order By: Relevance
“…Numerous studies have shown the benefits of mulch as a weed control tool (Altland et al, 2016;Bartley et al, 2017;Marble et al, 2019;Richardson et al, 2008). In contrast to mulch, which is applied on the substrate surface after planting, a stratified substrate would be part of the growing substrate (crop roots planted into the top stratified layer).…”
mentioning
confidence: 99%
“…Numerous studies have shown the benefits of mulch as a weed control tool (Altland et al, 2016;Bartley et al, 2017;Marble et al, 2019;Richardson et al, 2008). In contrast to mulch, which is applied on the substrate surface after planting, a stratified substrate would be part of the growing substrate (crop roots planted into the top stratified layer).…”
mentioning
confidence: 99%
“…Weed control efficacy is critical to selecting a mulch, but other factors such as application depth and chemical properties should be considered to ensure there are no negative effects on root development. Reports of mulch use in nursery container production have shown similar or increased plant growth compared with nonmulched plants (Marble et al, 2019). Few studies have evaluated mulches in propagation, but Witcher and Poudel (2020) reported several mulches (pine pellets, paper pellets, and rice hulls) had no effect on rooting of cuttings when applied at 0.3-inch depth.…”
mentioning
confidence: 99%
“…Later, mulches stood out among other non-chemical practices and became a research hot spot due to their easy availability and low prices (Chalker-Scott, 2007). The widely tested mulches, such as pine bark, rice hull, Douglas fir bark, coconut coir, newspaper pellets, and waste paper (Pellett and Heleba, 1995;Penny and Neal, 2003;Amoroso et al, 2009;Mathers and Case, 2010;Chen et al, 2013;Marble, 2015;Bartley et al, 2017;Burrows, 2017;Masilamany et al, 2017;Marble et al, 2019;Massa et al, 2019). Adding mulches (2.54-7.62 cm) can reach satisfactory weed control results depending on mulch types and weed species (Richardson et al, 2008;Cochran et al, 2009;Altland et al, 2016;Massa et al, 2019;Särkkä and Tahvonen, 2020).…”
Section: Research Trend In Nursery Weed Controlmentioning
confidence: 99%
“…To control weeds, various methods have been tested, such as chemical, non-chemical, and the integrated chemical and non-chemical practices (Marble, 2015;Stewart et al, 2017). Chemical weed control primarily uses herbicides to control weeds (Altland et al, 2004) whereas non-chemical weed control utilizes different cultural practices, such as mulching, irrigation, and fertilization to reduce the weed growth (Case et al, 2005;Amoroso et al, 2009;Marble et al, 2019;Saha et al, 2019b). To reduce herbicide usage while maintaining the promising weed control results, combined chemical and non-chemical weed control have been widely developed (Altland et al, 2004;Stewart et al, 2018).…”
Section: Introductionmentioning
confidence: 99%